Polymer nanocomposites based on inorganic and organic nanomaterials - Mohanty, Smita, 1976-; Nayak, Sanjay K.; Kaith, B. S.; Kalia, Susheel (Beverly, MA : Scrivener Publishing, 2015)
This book covers all aspects of the different classes of nanomaterials - from synthesis to application. It investigates in detail the use and feasibility of developing nanocomposites with these nanomaterials as reinforcements. The book encompasses synthesis and properties of cellulose nanofibers, bacterial nanocellulose, carbon nanotubes / nanofibers, graphene, nanodiamonds, nanoclays, inorganic nanomaterials and their nanocomposites for high-end applications such as electronic devices, energy storage, structural and packaging.
Samantara / Jagdeep Mohanta / Bikash Kumar Jena / Satyabrata Si -- 5.6.1. Optical Property / Subash Chandra Sahu / Aneeya K. Samantara / Jagdeep Mohanta / Bikash Kumar Jena / Satyabrata Si -- 5.6.2. Electrical Property / Subash Chandra Sahu / Aneeya K. Samantara / Jagdeep Mohanta / Bikash Kumar Jena / Satyabrata Si -- 5.6.3. Electronic Properties / Subash Chandra Sahu / Aneeya K. Samantara / Jagdeep Mohanta / Bikash Kumar Jena / Satyabrata Si -- 5.6.4. Quantum Hall Effect / Subash Chandra Sahu / Aneeya K. Samantara / Jagdeep Mohanta / Bikash Kumar Jena / Satyabrata Si -- 5.6.5. Mechanical Property / Subash Chandra Sahu / Aneeya K. Samantara / Jagdeep Mohanta / Bikash Kumar Jena / Satyabrata Si -- 5.6.6. Thermal and Thermoelectric Properties / Subash Chandra Sahu / Aneeya K. Samantara / Jagdeep Mohanta / Bikash Kumar Jena / Satyabrata Si -- 5.7. Synthesis of Graphene / Satyabrata Si / Subash Chandra Sahu / Aneeya K. Samantara / Jagdeep Mohanta / Bikash Kumar Jena -- 5.8. Biomedical Application of Graphene / Subash Chandra Sahu / Aneeya K. Samantara / Jagdeep Mohanta / Bikash Kumar Jena / Satyabrata Si -- 5.8.1. Graphene in Drug and Gene Delivery / Subash Chandra Sahu / Aneeya K. Samantara / Jagdeep Mohanta / Bikash Kumar Jena / Satyabrata Si -- 5.8.2. Graphene in Cancer Therapy / Subash Chandra Sahu / Aneeya K. Samantara / Jagdeep Mohanta / Bikash Kumar Jena / Satyabrata Si -- 5.8.3. Graphene in Bioimaging / Subash Chandra Sahu / Aneeya K. Samantara / Jagdeep Mohanta / Bikash Kumar Jena / Satyabrata Si -- 5.8.4. Graphene in Chemo- and Biosensing / Subash Chandra Sahu / Aneeya K. Samantara / Jagdeep Mohanta / Bikash Kumar Jena / Satyabrata Si -- 5.9. Graphene in Energy / Subash Chandra Sahu / Aneeya K. Samantara / Jagdeep Mohanta / Bikash Kumar Jena / Satyabrata Si -- 5.9.1. Graphene in Lithium Ion Battery / Subash Chandra Sahu / Aneeya K. Samantara / Jagdeep Mohanta / Bikash Kumar Jena / Satyabrata Si -- 5.9.2. Graphene in Fuel Cells / Subash Chandra Sahu / Aneeya K. Samantara / Jagdeep Mohanta / Bikash Kumar Jena / Satyabrata Si.
Includes bibliographical references and index.
Print version record.
Keywords: Nanostructured materials; Nanocomposites (Materials); Nanotechnology; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; TECHNOLOGY & ENGINEERING -- Nanotechnology & MEMS; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; SCIENCE -- Nanostructures; Nanostructured materials; Electronic books